Tracheoesophageal Puncture with Voice Prosthesis after Total Laryngectomy - Lulu Irlina (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2025)
Tracheoesophageal Puncture (TEP) is a widely used method for alaryngeal voice restoration following total laryngectomy. This procedure involves creating a fistula between the trachea and esophagus, enabling voice production through a voice prosthesis. The article reviews key factors influencing surgical outcomes, including timing of TEP (primary at laryngectomy vs. secondary at a later stage), radiation therapy, and reconstruction techniques. Primary TEP allows earlier voice rehabilitation but may increase perioperative risks, particularly in irradiated patients or complex reconstructions. Secondary TEP offers greater control of timing but delays speech restoration. Complications include fistula enlargement, leakage, infection, and prosthesis-related issues, with risks heightened by poor tissue vascularity and prior radiation. Speech outcomes are generally favorable, with many patients achieving functional communication, though performance varies with patient health, surgical expertise, and postoperative care. The authors emphasize individualized decision-making, weighing oncologic, functional, and patient-specific factors to optimize results. TEP remains a gold standard for alaryngeal speech, with careful management essential to minimize complications and maximize long-term function.